Mechanism for Financing the Accumulated Debt of Utility Services Water, Electricity and Gas as a Result of the Covid-19 - Becker-Cares, C; Verdejo-Fredes, H; Garcia-Munoz, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The effects associated with the pandemic of COVID-19 have left several consequences. The large confinements have caused formal and independent job losses. Therefore, families have been forced to prioritize their monthly utility bills. Most countries have decided on suspending cuts in utility services and give them payment arrangements for the future instead. In this article, the actions taken in Latin America and Europe are presented. Additionally, for the Chilean case, a mechanism for financing the accumulated debt is proposed. The main objective of this is to establish a procedure that allows users to regain the habit of paying for public utilities (water, electricity and piped gas). © 2022 by the authors. Licensee MDPI, Basel, Switzerland.